2020
DOI: 10.1186/s13014-020-01490-x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid V50 is a risk factor for hypothyroidism in patients with nasopharyngeal carcinoma treated with intensity-modulated radiation therapy: a retrospective study

Abstract: Background: We investigated the risk factors of radiation-induced thyroid dysfunction, then combined the clinical factors and optimum thyroid dosimetric parameters to predict the incidence rate of hypothyroidism (HT) and to guide individualized treatment. Methods: A total of 206 patients with histologically proven nasopharyngeal carcinoma (NPC) treated at the Cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Specifically, the N-stage represents lymph nodes stage, which refers to the size and extent of cervical lymph node metastasis. In our previous study, Nstage was an independent predictor of the incidence of HT [7], which is consistent with other studies [8,9]. Nonetheless, the relationship between N-stage and incidence of HT is still controversial, and as yet, there is no independent study to explore its internal relationship.…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, the N-stage represents lymph nodes stage, which refers to the size and extent of cervical lymph node metastasis. In our previous study, Nstage was an independent predictor of the incidence of HT [7], which is consistent with other studies [8,9]. Nonetheless, the relationship between N-stage and incidence of HT is still controversial, and as yet, there is no independent study to explore its internal relationship.…”
Section: Introductionsupporting
confidence: 89%
“…In contrast with the aforementioned conclusion, Koc and Capoglu [16] suggested that the clinical stage of NPC has no effect on the incidence of HT. In our previous study, N-stage played a major role in the NTCP model for predicting HT in NPC patients, and the incidence of HT in N 2-3 patients and N 0-1 patients was 58.82% and 44.29%, respectively [7]. e results of this study showed that N-stage can predict the incidence of HT again, and patients with advanced N-stage will inevitably receive higher irradiated volume of the tumor, resulting in a higher risk of thyroid irradiation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…V45 = 50% is the threshold for hypothyroidism ( 17 ), and subsequent meta-analysis results additionally support this conclusion ( 18 ). However, some studies believe that V30 or V50 is the dose threshold for hypothyroidism ( 19 – 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…The included studies were published from 2010 to 2021 across 13 countries, and all studies were observational in design. Nineteen studies provided comparative data on radiation dose-volume predictors (Table 1) [8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], while 10 studies reported radiation dosimetric nomograms or normal tissue complication probability (NTCP) models for post-radiation primary hypothyroidism (Table 2) [28][29][30][31][32][33][34][35][36][37]. The primary tumors were nasopharyngeal carcinoma (NPC), oropharyngeal carcinoma (OPC), and other sites in 41.4 % (12/29), 17.2 % (5/29), and 41.4 % (12/29) of the studies, respectively.…”
Section: Included Studiesmentioning
confidence: 99%